Impact of ripening on the physical properties of mango purees and application of simultaneous rheometry and in situ FTIR spectroscopy for rapid identification of biochemical and rheological changes. (July 2021) - Labaky, Paola; Dahdouh, Layal; Ricci, Julien; Wisniewski, Christelle; Pallet, Dominique; Louka, Nicolas; Grosmaire, Lidwine
Abstract: This study proposed to investigate the impact of ripening on the physical properties of mango purees. An extensive study of the particle size and rheological properties of mango purees and their dispersed phase was performed using particle size measurements, small deformation rheology, and an innovative technology combining simultaneous rheometry and in situ FTIR spectroscopy. The results revealed a sharp decrease in the solid-like behavior of mango purees, as well as in the energy of cohesion of their dispersed phase during the first 10 days of ripening, leading to a weakening of their gel-structure. The size of suspended insoluble solids in the purees continued to decrease until 15 days of ripening. According to the spectral fingerprints, it was possible to identify some changes in the purees' sugar content occurring upon the physical changes during ripening. The highest sucrose and lowest fructose contents were observed in purees obtained during the first 10 days of ripening, in comparison with the following days. Based on the twin physical and spectral fingerprints, purees obtained from the early days of ripening (<10 days) could be distinguished from other purees. Highlights: The cohesion energy and size of puree particles decreased during ripening. The gel structure and network strength of puree weakened during ripening. High sucrose and low fructose contents characterized purees <10 days of ripening. Purees obtained before day 10 of ripening could be distinguished from other purees.